Cho Problem in Hoshiarpur District - Sethi, C. M. (Indian Forester, 1960)
This article describes the cho problem in Hoshiarpur district. This is considered as problem No. l’ of the area. It narrates in detail the causes and the extent of the menace it has brought to this land which was once called the "garden district",of the Punjab State. It further deals with the remedial measures under the two main heads: PREVENTIVE and PROTECTIVE. It also discusses the efficacy of cho control schemes of the Punjab Irrigation Department.